Simbolisme dan Metafora dalam Cerpen “Hujan Bulan Juni” Karya Sapardi Djoko Damono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the form and meaning of symbolism and metaphor in the short story Hujan Bulan Juni by Sapardi Djoko Damono. This study is motivated by the richness of figurative language in Sapardi's work which reflects feelings, experiences, and life values ​​through a distinctive style of speech. The research method used is descriptive qualitative with content analysis techniques, including identification, classification, and interpretation of data based on stylistic and semiotic theories. The data source for this study is the text of the short story Hujan Bulan Juni published in Sapardi's collection of works. The results of the study show that symbolism in this short story is mostly manifested through the use of natural objects such as rain, the moon, and seasons as symbols of patience, waiting, and suppressed longing. Meanwhile, metaphors are used to strengthen the inner atmosphere of the characters, describe emotional relationships, and imply philosophical messages about sincere and sacrificial love. The conclusion of this study is that the symbolism and metaphor in the short story Hujan Bulan Juni not only beautify the language, but also function as a means of conveying moral messages and profound aesthetic values. These findings can be a reference for learning literary appreciation, especially in the material on analyzing language styles in short stories at elementary, high school and university levels.